Laser-induced microstructural development and phase evolution in magnesium alloy - Guan, Yingchun (2016)
Secondary phase plays an important role in determining microstructures and properties of magnesium alloys. This paper focuses on laser-induced microstructure development and secondary phase evolution in AZ91D Mg alloy studied by SEM, TEM and EDS analyses. Compared to bulk shape and lamellar structure of the secondary phase in as-received cast material, rapid-solidified microstructures with various morphologies including nano-precipitates were observed in laser melt zone. Formation mechanisms of microstructural evolution and effect of phase development on surface properties were further discussed.